Squid, Illex illecebrosus (LeSueur), in the Newfoundland Fishing Area - Squires, H. J. (Journal of the Fisheries Research Board of Canada, 1957)
Data from incidental trawl catches of squid by the research vessel, Investigator II, showed that distribution of Illex in the Newfoundland area was marked by a seasonal migration over the Grand Banks in early May, and northward and westward as far as Hamilton Inlet, Labrador, and inshore Newfoundland by August. Earliest occurrence inshore was in late June, earlier in recent years than heretofore. Comparative numbers taken on the Grand Bank in May and June in different years appear to indicate the abundance to arrive inshore later in each year. Annual abundance inshore varies, but years of scarcity do not appear to be cyclical nor need they indicate year-class failure. A correlation between abundance inshore and weather conditions may exist. Measurements during the inshore migration showed a regular and large increment of length and weight monthly until October. Female squid reached a greater size than males in the late season but weighed less than males at the same mantle length. Fin length was 35 to 40% of mantle length in Illex, compared with 53 to 63% in Loligo pealii. Many males taken in the late season had reached sexual maturity, but only two females captured on the Grand Bank in May, 1953, had reached equivalent maturity: these females had greatly enlarged nidamental glands.Small squid taken offshore in 1946 to 1952 had been feeding mostly on euphausids, but larger squid taken inshore had been feeding mostly on fish. In females 44% of the stomachs were empty, and in males, 50%.Parasites found were tapeworm plerocercoids of Phyllobothrium sp. and Dinobothrium (sensu lato) sp., and occasionally a small larval nematode.